USE OF F-MATH MEDIA WITH A RELIGIOUS NUANCE AND STUDENTS' CREATIVE THINKING ABILITIES ON COGNITIVE AND AFFECTIVE ABILITIES IN MATHEMATICS LEARNING - Agus Miftakus Surur; Henry Praherdhiono; M Ubaidillah Ridwanulloh; M Khoiril Akhyar; Sri Pujilestari (Universitas Muhammadiyah Lampung, 2025)
Social media has a strong appeal to today's young generation. The use of social media with religious nuances in f-math can provide context that is relevant to religious values, so that students can connect mathematics with moral principles and have a positive perception of mathematics learning. The use of social media-based f-math media can also influence students' cognitive abilities in understanding mathematical concepts. With dynamic interactions and attractive visuals, students tend to be more interested and participate more actively in mathematics learning. Apart from that, the use of social media in mathematics learning can influence students' affective abilities. Active involvement in use so that students' level of confidence and motivation can increase. This can lead to the formation of a positive attitude towards mathematics and increase self-confidence in solving mathematical problems. The use of f-math media based on social media with religious nuances can have a positive influence on students' creative thinking abilities as well as cognitive and affective abilities in learning mathematics. By utilizing the appeal of social media and emphasizing the relevance of mathematics to religious values, students can view mathematics more positively and develop their creative thinking skills in solving mathematical problems.